Intelligent composite material diaphragm as well as preparation method and application thereof
By using a smart composite separator with shape memory polymer foam skeleton and gel electrolyte in the battery separator, the problems of slow response speed and high energy consumption of existing battery thermal management methods are solved, intelligent independent power regulation and over-temperature protection are achieved, and the safety and service life of the battery are improved.
Patent Information
- Application Number
- CN202510037266.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing battery thermal management methods have shortages such as slow response speed, complex equipment, and increased overall energy consumption of the system, which is difficult to meet the needs of intelligent, fast response and efficient thermal management in modern battery application scenarios.
Using a smart composite separator, which consists of a shape memory polymer foam skeleton and gel electrolyte, can independently adjust the battery power output and provide overtemperature protection.
It realizes thermal management that responds in real-time according to temperature changes during the battery operation, has intelligent independent power regulation and over-temperature protection functions, and improves the safety and service life of the battery.
Smart Images

Figure CN119833884A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery diaphragm materials, and in particular relates to an intelligent composite material diaphragm and a preparation method and application thereof. Background Art
[0002] With the rapid development of battery technology and its wide application in various application scenarios, battery thermal management and safety issues have gradually become the focus of research and industry attention. Especially in the use of high-power and high-energy density batteries, thermal runaway inside the battery will not only affect its performance, but may also lead to serious safety accidents. Therefore, how to effectively solve the problem of thermal protection of batteries under high temperature conditions is crucial to improving the overall safety and service life of the battery.
[0003] Traditional battery thermal management methods mainly rely on external cooling devices, such as fans or liquid cooling systems. Although these methods can help cool the battery to a certain extent, they have shortcomings such as slow response speed, complex equipment, and increased overall system energy consumption, making it difficult to meet the needs of modern battery application scenarios for intelligent, fast response, and efficient thermal management.
[0004] In summary, it is very necessary to provide an intelligent composite material diaphragm with intelligent autonomous power regulation and over-temperature protection, and a preparation method and application thereof. Summary of the invention
[0005] In order to solve one or more technical problems existing in the prior art, the present invention provides an intelligent composite material diaphragm and its preparation method and application. The intelligent composite material diaphragm in the present invention has the functions of autonomously adjusting battery power output and over-temperature protection, and can be used for thermal management and safety protection of high energy density batteries; the intelligent composite material diaphragm in the present invention can be widely used in electric vehicles, energy storage equipment and other application scenarios with high requirements for efficient thermal management and safety.
[0006] The present invention provides an intelligent composite material diaphragm in a first aspect, the intelligent composite material diaphragm comprising a shape memory polymer foam skeleton and a gel electrolyte filled in the shape memory polymer foam skeleton; the raw materials for preparing the shape memory polymer foam skeleton comprise epoxy resin and D-230 curing agent; the raw materials for preparing the gel electrolyte comprise N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate, tetramethylethylenediamine and a lithium salt solution.
[0007] Preferably, the epoxy resin is E-44 epoxy resin; and / or the mass ratio of the epoxy resin to the D-230 curing agent is (9-15):(3-5).
[0008] Preferably, the usage ratio of the N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate and tetramethylethylenediamine is (0.28-0.33) g: (10-18) mg: (3-4) mg: (5-6) mg: (18-20) μL; and / or the mass ratio of the total mass of the N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide and ammonium persulfate to the mass ratio of the lithium salt solution is 1: (5-20).
[0009] Preferably, the concentration of the lithium salt solution is 1-2 mol / L; the lithium salt solution is obtained by mixing a lithium salt and a solvent; preferably, the lithium salt is selected from one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonate)imide, tris(trifluoromethylsulfonate)methyl lithium and lithium bis(oxalatoborate); preferably, the solvent is a carbonate compound, more preferably, the carbonate compound is selected from one or more of propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
[0010] In a second aspect, the present invention provides a method for preparing the smart composite material diaphragm according to the first aspect of the present invention, the method comprising the following steps:
[0011] (1) mixing epoxy resin and D-230 curing agent evenly to obtain a first mixed solution, then infiltrating the first mixed solution into a salt template, and then curing, after the curing is completed, removing the salt template and drying to obtain a shape memory polymer foam skeleton;
[0012] (2) compressing the shape memory polymer foam skeleton to obtain a compressed shape memory polymer foam skeleton;
[0013] (3) N-isopropyl acrylamide, acrylamide, N,N'-methylenebisacrylamide, and ammonium persulfate are dispersed in a lithium salt solution to obtain a second mixed solution, and then a compressed shape memory polymer foam skeleton is immersed in the second mixed solution and tetramethylethylenediamine is added to react to obtain an intelligent composite material diaphragm.
[0014] Preferably, the curing is firstly curing at 70-90° C. for 1-3 hours, and then curing at 120-140° C. for 1-3 hours.
[0015] Preferably, the reaction time is 5 to 10 minutes.
[0016] Preferably, the response temperature of the shape memory polymer foam skeleton is 100-150°C; and / or the response temperature of the gel electrolyte filled in the shape memory polymer foam skeleton is 40-58°C.
[0017] Preferably, the intelligent composite material diaphragm has intelligent autonomous power regulation function and over-temperature protection function.
[0018] The third aspect of the present invention provides the use of the smart composite material diaphragm described in the first aspect of the present invention or the smart composite material diaphragm prepared by the preparation method described in the second aspect of the present invention in a lithium ion battery.
[0019] Compared with the prior art, the present invention has at least the following beneficial effects:
[0020] (1) The intelligent composite material diaphragm provided by the present invention is a thermal management composite material diaphragm suitable for lithium-ion batteries with intelligent autonomous control function (including intelligent autonomous power control function and over-temperature protection function). The intelligent composite material diaphragm described in the present invention includes a shape memory polymer foam skeleton and a gel electrolyte, which can respond in real time according to temperature changes during battery operation, and adjust ionic conductivity to control battery output power; when the battery temperature rises, the gel electrolyte shrinks (gel electrolyte pores are closed), reducing the power output of the battery; when the temperature drops, the gel electrolyte pores recover (pores open), improving the power output of the battery; in addition, the shape memory polymer foam skeleton can automatically restore its original shape at extremely high temperatures, thereby cutting off the battery circuit and providing over-temperature protection, while other polymer foam skeletons do not have the unique temperature response characteristics of shape memory foam, and cannot forcibly cut off the power of the battery at high temperatures; at the same time, the shape memory foam also has the function of inhibiting the growth of lithium dendrites, thereby extending the battery life. The intelligent composite material diaphragm of the present invention has an autonomous thermal protection function and is particularly suitable for battery application scenarios with high energy density and high safety requirements.
[0021] (2) The present invention fills the gel electrolyte in a shape memory polymer foam skeleton. The pore wall structure of the shape memory polymer foam skeleton is stable and can provide effective support for the gel electrolyte. When the battery temperature rises, it can exert a certain resistance to the contraction of the gel electrolyte to avoid excessive closure of the pores due to contraction. When the battery temperature drops, the support effect ensures that the gel electrolyte pores will not deform or expand uncontrollably during the recovery process, thereby providing a continuous constrained environment for the gel electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1is a SEM image of the gel electrolyte included in the smart composite material separator of the present invention in the pore-opening state and the pore-closing state;
[0024] Figure 2 Schematic diagram of the transformation between the original shape and the deformed shape of the shape memory polymer foam skeleton (SMP foam) in the present invention; Figure 2 In the figure, (a) is a schematic diagram of the temperature response of the SMP foam that has not been filled with gel electrolyte. The deformed shape in Figure (a) is a schematic diagram of the shape memory polymer foam skeleton made with a salt template, and the original shape in Figure (a) is a schematic diagram of the compressed shape memory polymer foam skeleton; Figures (b) to (d) show the temperature response process of the gel electrolyte after the compressed shape memory polymer foam skeleton is filled with gel electrolyte. As the temperature rises, the pores of the gel electrolyte gradually close and the ionic conductivity decreases;
[0025] Figure 3 It is a schematic diagram of assembling a battery with the smart composite material diaphragm and electrodes in the present invention. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] The present invention provides an intelligent composite material diaphragm in a first aspect, the intelligent composite material diaphragm comprising a shape memory polymer foam skeleton and a gel electrolyte filled in the shape memory polymer foam skeleton; the raw materials for preparing the shape memory polymer foam skeleton comprise epoxy resin and D-230 curing agent; the raw materials for preparing the gel electrolyte comprise N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate, tetramethylethylenediamine and a lithium salt solution.
[0028] The present invention proposes an autonomous thermal protection solution, which uses an intelligent composite material as a battery separator, which can respond and adjust in real time according to temperature changes during battery operation, and has a more intelligent thermal management function; the gel electrolyte inside the intelligent composite material separator in the present invention is combined with the shape memory polymer foam, which can not only autonomously adjust the power output of the battery to prevent overheating, but also can cut off the circuit through the shape memory function of the shape memory polymer foam skeleton when the temperature rises abnormally, provide over-temperature protection, and greatly improve the safety performance of the battery; the present invention finds that the shape memory polymer foam material used can also inhibit the growth of lithium dendrites, delay the battery's degradation, and further extend the battery's service life. The growth of lithium dendrites is a common phenomenon in the charging and discharging process of lithium batteries, especially in high energy density batteries. The formation of lithium dendrites will pierce the separator, causing the battery to short-circuit, increasing the risk of battery failure and thermal runaway. The present invention can effectively prevent the growth of lithium dendrites by introducing a shape memory polymer foam skeleton, improve the safety and stability of the battery in long-term use, and extend the battery's service life. In addition, the present invention has found that filling a gel electrolyte that can respond in real time to temperature changes into a shape memory polymer foam skeleton can also more effectively inhibit the growth of lithium dendrites, which is beneficial to improving the cycle stability of the battery.
[0029] With the continuous increase in demand for high-performance batteries in the fields of electric vehicles, smart devices, energy storage systems, etc., thermal management composite material diaphragms with intelligent control functions will show broad application prospects in these key fields. The technology of the present invention is not only expected to significantly improve the safety and life of the battery, but also to reduce the dependence on the external cooling system, thereby simplifying the system design, reducing manufacturing costs, and promoting the development of the next generation of high-efficiency battery technology. In addition, in future wearable devices, aerospace vehicles and other application scenarios with extremely high requirements for lightweight and high safety, the intelligent composite composite material diaphragm of the present invention also has great potential value, further promoting the upgrading of energy storage technology. The intelligent composite composite material diaphragm based on autonomous thermal management in the present invention not only overcomes the shortcomings of the traditional external cooling system, but also realizes more efficient and rapid thermal protection and life extension functions through the internal intelligent control mechanism, which meets the requirements of future battery technology for high safety and high life, and has important development prospects in a wide range of application scenarios.
[0030] According to some preferred embodiments, the epoxy resin is E-44 epoxy resin; and / or the mass ratio of the epoxy resin to the D-230 curing agent (D230 curing agent) is (9-15): (3-5); in the present invention, by adjusting the ratio of the epoxy resin (preferably E-44 epoxy resin) to the D-230 curing agent in the shape memory polymer foam skeleton, the response temperature of the shape memory polymer foam can be controlled. Preferably, the mass ratio of the epoxy resin to the D-230 curing agent is (9-15): (3-5), and a shape memory polymer foam skeleton with a response temperature of 100-150°C, preferably 100-120°C, can be obtained; the present invention finds that if the content of the D-230 curing agent is too small, the epoxy resin will not be cured and remain in a liquid state, and if the content of the D-230 curing agent is too high, excess curing agent will exist in the network, resulting in a decrease in the overall strength of the material.
[0031] According to some preferred embodiments, the dosage ratio of N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate, and tetramethylethylenediamine is (0.28-0.33) g: (10-18) mg: (3-4) mg: (5-6) mg: (18-20) μL; In the present invention, by adjusting the content of acrylamide (AM) in the gel electrolyte, the thermal response temperature of the gel electrolyte can be effectively regulated; the higher the AM content, the lower the gel response temperature, but its content should be lower than that of N-isopropylacrylamide (NIPAM) 10% of the total mass, preferably, the mass ratio of the N-isopropylacrylamide to the acrylamide is controlled to be (0.28-0.33) g: (10-18) mg, so that the response temperature of the gel electrolyte filled in the shape memory polymer foam skeleton is 40-58° C., so that the smart composite material diaphragm of the present invention is more applicable in lithium ion batteries; and / or the total mass ratio of the N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide and ammonium persulfate to the lithium salt solution is 1: (5-20).
[0032] According to some preferred embodiments, the concentration of the lithium salt solution is 1-2 mol / L; the lithium salt solution is obtained by mixing a lithium salt and a solvent; preferably, the lithium salt is selected from one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonate)imide, tris(trifluoromethylsulfonate)methyl lithium and lithium bis(oxalatoborate); preferably, the solvent is a carbonate compound, and more preferably, the carbonate compound is selected from one or more of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate; in order to achieve temperature response regulation of the gel electrolyte, the gel electrolyte of the present invention is composed of a gel matrix and a lithium salt solution, and the lithium salt solution is obtained by mixing a lithium salt and a solvent. This configuration can not only ensure efficient ion conduction, but also can finely regulate the pore structure according to temperature changes to meet the battery power regulation requirements.
[0033] In a second aspect, the present invention provides a method for preparing the smart composite material diaphragm according to the first aspect of the present invention, the method comprising the following steps:
[0034] (1) The epoxy resin and the D-230 curing agent are mixed evenly to obtain a first mixed solution, and then the first mixed solution is infiltrated (immersed) into a salt template, and then cured. After the curing is completed, the salt template is removed and dried to obtain a shape memory polymer foam skeleton; the present invention does not specifically limit the preparation of the salt template, and those skilled in the art can make a conventional selection; in the present invention, the preparation of the salt template can be, for example, as follows: a mixture of sodium chloride NaCl, polyvinyl pyrrolidone, lithium sulfate and manganese sulfate is dispersed in deionized water to form a uniform aqueous solution; after freezing the solution, small sodium chloride crystals are formed and assembled into a template, and then the water is removed by freeze drying; wherein the mass ratio of NaCl, polyvinyl pyrrolidone, lithium sulfate and manganese sulfate is, for example, 10:1:0.5:0.5, and the amount of deionized water can be, for example, 20 to 25 times the mass of the mixture of sodium chloride NaCl, polyvinyl pyrrolidone, lithium sulfate and manganese sulfate;
[0035] (2) compressing the shape memory polymer foam skeleton to obtain a compressed shape memory polymer foam skeleton; in the present invention, for example, the shape memory polymer foam skeleton obtained in step (1) can be compressed to a compressed shape memory polymer foam skeleton with a thickness of 0.5 to 1.5 mm, preferably compressed to a compressed shape memory polymer foam skeleton with a thickness of 1 mm;
[0036] (3) N-isopropylacrylamide (NIPAM), acrylamide (AM), N,N'-methylenebisacrylamide (MBA), and ammonium persulfate (APS) are dispersed in a lithium salt solution to obtain a second mixed solution, and then the compressed shape memory polymer foam skeleton is immersed (soaked) in the second mixed solution and tetramethylethylenediamine (TEMED) is added for reaction to obtain an intelligent composite material diaphragm; the present invention does not make a specific limitation on the usage ratio of the compressed shape memory polymer foam skeleton and the second mixed solution, so that the compressed shape memory polymer foam skeleton can be immersed in the second mixed solution.
[0037] The present invention provides a method for preparing an intelligent composite material diaphragm. The prepared intelligent composite material diaphragm is particularly suitable for thermal management of lithium batteries. The composite material diaphragm has the functions of autonomously adjusting power output and over-temperature protection, and can respond quickly when the internal temperature of the battery changes, ensuring the safety and efficient operation of the battery. The battery is thermally managed and over-temperature protected by the internal gel electrolyte and the shape memory polymer foam frame, respectively. Within the normal operating temperature range of the battery, the gel electrolyte in the intelligent composite material diaphragm can respond to the change of temperature, adjust its internal pore structure, and then change the ionic conductivity to achieve the regulation of the battery power. When the battery temperature rises, the gel electrolyte shrinks, the pores decrease, the ionic conductivity decreases, and the battery output power decreases accordingly, helping to control the battery temperature. When the battery temperature drops, the gel electrolyte pores recover, the ionic conductivity increases, and the battery power increases. In this way, the battery can maintain a stable output under different temperature conditions. When the temperature inside the battery rises sharply due to a short circuit or other faults, the shape memory polymer foam frame returns to its original form through its shape memory function, thereby physically cutting off the battery circuit, preventing overheating or explosion, providing reliable over-temperature protection for the battery, and extending the battery life.
[0038] According to some preferred embodiments, the curing is first cured at 70-90°C (e.g., 70°C, 80°C or 90°C) for 1-3h (e.g., 1, 2 or 3h), and then cured at 120-140°C (e.g., 120°C, 130°C or 140°C) for 1-3h (e.g., 1, 2 or 3h).
[0039] According to some specific embodiments, the E-44 epoxy resin and the D-230 curing agent are mixed evenly to obtain a first mixed solution, and the first mixed solution is infiltrated into the prepared salt template by vacuum impregnation, and then the salt template infiltrated with the first mixed solution is cured at 80°C for 2 hours, and then cured at 130°C for 2 hours. After the curing is completed, the salt template is removed (cleaned with deionized water to remove the salt template) and dried to obtain a shape memory polymer foam skeleton, which is then processed to a thickness of 1 mm. The specific processing operation is: heating the obtained shape memory polymer foam skeleton to above the response temperature, compressing it to a thickness of 1 mm and cooling it to shape it to obtain a compressed shape memory polymer foam skeleton; the present invention does not specifically limit the conditions of the vacuum impregnation method, and those skilled in the art can conventionally select, for example, the vacuum degree of vacuum impregnation is -0.1MPa to -0.09MPa, and the time of vacuum impregnation is 0.5 to 1h.
[0040] According to some preferred embodiments, the reaction time is 5 to 10 minutes. In the present invention, after adding tetramethylethylenediamine, the reaction is initiated at room temperature, for example, room temperature 15 to 35° C., and the reaction time is 5 to 10 minutes.
[0041] According to some specific embodiments, N-isopropylacrylamide (NIPAM), acrylamide (AM), N,N'-methylenebisacrylamide (MBA), and ammonium persulfate (APS) are dispersed in a lithium salt solution to obtain a second mixed solution, and then the compressed shape memory polymer foam skeleton is immersed (soaked in) the second mixed solution, and in a glove box environment, tetramethylethylenediamine (TEMED) is slowly added dropwise and rapidly stirred to react for 5 to 10 minutes, so that the pore structure of the compressed shape memory polymer foam skeleton is filled with a gel electrolyte to obtain a smart composite material diaphragm; in some specific embodiments, the preparation raw materials include 0.28g N-isopropylacrylamide (NIPAM), 15mg monomer acrylamide (AM), 3mg N,N'-methylenebisacrylamide (MBA) cross-linking agent, 5mg ammonium persulfate (APS) initiator, 18μL tetramethylethylenediamine (TEMED) and a lithium salt solution with a concentration of 1mol / L (with EC / PC as solvent). The present invention has no particular limitation on the speed of rapid stirring, and those skilled in the art may select the speed conventionally. For example, the stirring speed may be 600 to 2000 r / min.
[0042] According to some preferred embodiments, the response temperature of the shape memory polymer foam skeleton is 100-150°C, preferably 100-120°C; and / or the response temperature of the gel electrolyte filled in the shape memory polymer foam skeleton is 40-58°C.
[0043] According to some preferred embodiments, the smart composite material diaphragm has an intelligent autonomous power regulation function and an over-temperature protection function; in the present invention, the smart composite material diaphragm includes a shape memory polymer foam skeleton and a gel electrolyte filled in the shape memory polymer foam skeleton; under the condition of increased temperature, the pores of the filled gel electrolyte are closed to a certain extent, and under the condition of reduced temperature, the pores of the filled gel electrolyte are opened.
[0044] The third aspect of the present invention provides the use of the smart composite material diaphragm described in the first aspect of the present invention or the smart composite material diaphragm prepared by the preparation method described in the second aspect of the present invention in a lithium-ion battery; in the present invention, the prepared smart composite material diaphragm, a commercial lithium iron phosphate electrode (as a positive electrode) and a commercial graphite electrode (as a negative electrode) can be assembled to obtain a soft-pack battery with good thermal management performance and safety performance.
[0045] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments, and those skilled in the art may make various corresponding changes and deformations according to the present invention without departing from the spirit and essence of the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention.
[0046] Example 1
[0047] 10g of E-44 epoxy resin and 3.4g of D-230 curing agent were mixed evenly to obtain a first mixed solution, and the first mixed solution was infiltrated into the salt template by vacuum impregnation, and then the salt template infiltrated with the first mixed solution was cured at 80°C for 2 hours, and then cured at 130°C for 2 hours. After the curing is completed, the salt template is removed (cleaned with deionized water to remove the salt template) and dried to obtain a shape memory polymer foam skeleton, which is then processed to a thickness of 1mm, specifically, it is heated to 120°C, compressed to a thickness of 1mm, and cooled to set, to obtain a compressed shape memory polymer foam skeleton; 0.33g of N-isopropylacrylamide (NIPAM), 17.36mg of acrylamide (AM), 4mg N,N'-methylenebisacrylamide (MBA) and 6 mg of ammonium persulfate (APS) are dispersed in a lithium salt solution to obtain a second mixed solution, and then a compressed shape memory polymer foam skeleton is placed in the second mixed solution, and in a glove box environment, 20 μL of tetramethylethylenediamine (TEMED) is slowly added and stirred for reaction for 10 minutes to obtain an intelligent composite material diaphragm with a gel electrolyte filled with a shape memory polymer foam skeleton; wherein the total mass ratio of the N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide and ammonium persulfate to the lithium salt solution is 1:15, the lithium salt solution is a mixture of lithium hexafluorophosphate and a solvent, the solvent is composed of ethylene carbonate and propylene carbonate in a mass ratio of 1:1, and the concentration of lithium hexafluorophosphate in the lithium salt solution is 1 mol / L.
[0048] In the smart composite material separator prepared in this embodiment, the response temperature of the shape memory polymer foam skeleton is 100°C, and the response temperature of the filled gel electrolyte is 42°C.
[0049] Example 2
[0050] 12g of E-44 epoxy resin and 4g of D-230 curing agent were mixed evenly to obtain a first mixed solution, and the first mixed solution was infiltrated into the salt template by vacuum impregnation, and then the salt template infiltrated with the first mixed solution was cured at 80°C for 2 hours, and then cured at 130°C for 2 hours. After the curing was completed, the salt template was removed (cleaned with deionized water to remove the salt template) and dried to obtain a shape memory polymer foam skeleton, which was then processed to a thickness of 1mm, specifically, it was heated to 150°C and compressed to a thickness of 1mm and cooled to set, to obtain a compressed shape memory polymer foam skeleton; 0.33g of N-isopropylacrylamide (NIPAM), 17.36mg of acrylamide (AM), 4mg N,N'-methylenebisacrylamide (MBA) and 6 mg of ammonium persulfate (APS) are dispersed in a lithium salt solution to obtain a second mixed solution, and then a compressed shape memory polymer foam skeleton is placed in the second mixed solution, and in a glove box environment, 20 μL of tetramethylethylenediamine (TEMED) is slowly added and stirred for reaction for 10 minutes to obtain an intelligent composite material diaphragm with a gel electrolyte filled with a shape memory polymer foam skeleton; wherein the total mass ratio of the N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide and ammonium persulfate to the lithium salt solution is 1:15, the lithium salt solution is a mixture of lithium hexafluorophosphate and a solvent, the solvent is composed of ethylene carbonate and propylene carbonate in a mass ratio of 1:1, and the concentration of lithium hexafluorophosphate in the lithium salt solution is 1 mol / L.
[0051] In the smart composite material separator prepared in this embodiment, the response temperature of the shape memory polymer foam skeleton is 120°C, and the response temperature of the filled gel electrolyte is 42°C.
[0052] Example 3
[0053] 10g of E-44 epoxy resin and 3.4g of D-230 curing agent were mixed evenly to obtain a first mixed solution, and the first mixed solution was infiltrated into the salt template by vacuum impregnation, and then the salt template infiltrated with the first mixed solution was cured at 80°C for 2 hours, and then cured at 130°C for 2 hours. After the curing is completed, the salt template is removed (cleaned with deionized water to remove the salt template) and dried to obtain a shape memory polymer foam skeleton, which is then processed to a thickness of 1mm, specifically, it is heated to 120°C, compressed to a thickness of 1mm, and cooled to set, to obtain a compressed shape memory polymer foam skeleton; 0.3g of N-isopropylacrylamide (NIPAM), 14.5mg of acrylamide (AM), 4mg N,N'-methylenebisacrylamide (MBA) and 6 mg of ammonium persulfate (APS) are dispersed in a lithium salt solution to obtain a second mixed solution, and then a compressed shape memory polymer foam skeleton is placed in the second mixed solution, and in a glove box environment, 20 μL of tetramethylethylenediamine (TEMED) is slowly added and stirred for reaction for 10 minutes to obtain an intelligent composite material diaphragm with a gel electrolyte filled with a shape memory polymer foam skeleton; wherein the total mass ratio of the N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide and ammonium persulfate to the lithium salt solution is 1:15, the lithium salt solution is a mixture of lithium hexafluorophosphate and a solvent, the solvent is composed of ethylene carbonate and propylene carbonate in a mass ratio of 1:1, and the concentration of lithium hexafluorophosphate in the lithium salt solution is 1 mol / L.
[0054] In the smart composite material separator prepared in this embodiment, the response temperature of the shape memory polymer foam skeleton is 100° C., and the response temperature of the filled gel electrolyte is adjusted to 50° C. by reducing the AM content.
[0055] Example 4
[0056] 10g of E-44 epoxy resin and 3.4g of D-230 curing agent were mixed evenly to obtain a first mixed solution, and the first mixed solution was infiltrated into the salt template by vacuum impregnation, and then the salt template infiltrated with the first mixed solution was cured at 80°C for 2 hours, and then cured at 130°C for 2 hours. After the curing is completed, the salt template is removed (cleaned with deionized water to remove the salt template) and dried to obtain a shape memory polymer foam skeleton, which is then processed to a thickness of 1mm, specifically, it is heated to 120°C, compressed to a thickness of 1mm, and cooled to set, to obtain a compressed shape memory polymer foam skeleton; 0.28g of N-isopropylacrylamide (NIPAM), 12mg of acrylamide (AM), 4mg N,N'-methylenebisacrylamide (MBA) and 6 mg of ammonium persulfate (APS) are dispersed in a lithium salt solution to obtain a second mixed solution, and then a compressed shape memory polymer foam skeleton is placed in the second mixed solution, and in a glove box environment, 20 μL of tetramethylethylenediamine (TEMED) is slowly added and stirred for reaction for 10 minutes to obtain an intelligent composite material diaphragm with a gel electrolyte filled with a shape memory polymer foam skeleton; wherein the total mass ratio of the N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide and ammonium persulfate to the lithium salt solution is 1:15, the lithium salt solution is a mixture of lithium hexafluorophosphate and a solvent, the solvent is composed of ethylene carbonate and propylene carbonate in a mass ratio of 1:1, and the concentration of lithium hexafluorophosphate in the lithium salt solution is 1 mol / L.
[0057] In the smart composite material separator prepared in this embodiment, the response temperature of the shape memory polymer foam skeleton is 100° C., and the response temperature of the filled gel electrolyte is adjusted to 58° C. by further reducing the AM content.
[0058] Comparative Example 1
[0059] 0.33 g N-isopropylacrylamide (NIPAM), 17.36 mg acrylamide (AM), 4 mg N,N'-methylenebisacrylamide (MBA), and 6 mg ammonium persulfate (APS) are dispersed in a lithium salt solution to obtain a mixed solution, and then an epoxy resin foam is placed in the mixed solution, and in a glove box environment, 20 μL of tetramethylethylenediamine (TEMED) is slowly added dropwise and stirred for reaction for 10 minutes to obtain a composite material diaphragm with a gel electrolyte filled with an epoxy resin foam skeleton; wherein the total mass ratio of the N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide and ammonium persulfate to the lithium salt solution is 1:15, the lithium salt solution is a mixture of lithium hexafluorophosphate and a solvent, the solvent is composed of ethylene carbonate and propylene carbonate in a mass ratio of 1:1, and the concentration of lithium hexafluorophosphate in the lithium salt solution is 1 mol / L.
[0060] In the composite material diaphragm prepared in this comparative example, the epoxy resin foam skeleton used has no temperature responsiveness and no effect of rapid power-off at high temperature. The response temperature of the filled gel electrolyte is 42°C.
[0061] Comparative Example 2
[0062] 10 g of E-44 epoxy resin and 3.4 g of D-230 curing agent were mixed evenly to obtain a first mixed solution, and the first mixed solution was infiltrated into the salt template by vacuum impregnation. The salt template infiltrated with the first mixture was then cured at 80° C. for 2 hours and then at 130° C. for 2 hours. After the curing is completed, the salt template is removed (cleaned with deionized water to remove the salt template) and dried to obtain a shape memory polymer foam skeleton, which is then processed to a thickness of 1 mm, specifically, it is heated to 120°C to be compressed to a thickness of 1 mm and cooled to be fixed to obtain a compressed shape memory polymer foam skeleton; bisphenol A dimethacrylate and a polyetheramine mixture are mixed with a lithium salt solution to obtain a mixed electrolyte solution, wherein the mass ratio of the bisphenol A dimethacrylate and polyetheramine mixture to the lithium salt solution is 1:1, and the mass ratio of bisphenol A dimethacrylate and polyetheramine is 3:1, and the lithium salt solution is a mixture of lithium hexafluorophosphate and a solvent, wherein the solvent is composed of ethylene carbonate and propylene carbonate in a mass ratio of 1:1, and the concentration of lithium hexafluorophosphate in the lithium salt solution is 1 mol / L; then the compressed shape memory polymer foam skeleton is placed in the mixed electrolyte solution and soaked for 48 hours, the soaked material is placed on a glass plate at room temperature, excess liquid on the surface is scraped off, and then allowed to stand for 48 hours until the mixed electrolyte solution is cross-linked to obtain a composite material diaphragm.
[0063] In the composite material diaphragm prepared in this comparative example, the response temperature of the shape memory polymer foam skeleton is 100° C., and the filled gel electrolyte has no temperature responsiveness.
[0064] The present invention tests the initial ionic conductivity of the composite film at room temperature 25°C, the ionic conductivity after decreasing when heated to 92°C, and the ionic conductivity after recovering when cooled to room temperature 25°C of the composite film obtained in each embodiment and each comparative example. The results are shown in Table 1.
[0065] Table 1
[0066]
[0067]
[0068] The present invention also assembles the smart composite material diaphragm prepared in Example 1 and the composite material diaphragm prepared in Comparative Examples 1 to 2 with commercial lithium iron phosphate electrodes (as positive electrodes) and commercial graphite electrodes (as negative electrodes) to obtain soft-pack batteries, and conducts performance tests. It is measured that the battery has a current density of 1 mA / cm 2 , specific capacity is 1 mAh / cm 2 The coulombic efficiency results at 200 cycles under the same conditions are shown in Table 2.
[0069] Table 2
[0070]
[0071] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A smart composite material diaphragm, characterized in that: The smart composite material separator comprises a shape memory polymer foam skeleton and a gel electrolyte filled in the shape memory polymer foam skeleton; The raw materials for preparing the shape memory polymer foam skeleton include epoxy resin and D-230 curing agent; The raw materials for preparing the gel electrolyte include N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate, tetramethylethylenediamine and lithium salt solution.
2. The smart composite material diaphragm according to claim 1, characterized in that: The epoxy resin is E-44 epoxy resin; and / or The mass ratio of the epoxy resin to the D-230 curing agent is (9-15):(3-5).
3. The smart composite material diaphragm according to claim 1, characterized in that: The dosage ratio of N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate and tetramethylethylenediamine is (0.28-0.33) g: (10-18) mg: (3-4) mg: (5-6) mg: (18-20) μL; and / or The mass ratio of the total mass of the N-isopropylacrylamide, acrylamide, N,N'-methylenebisacrylamide and ammonium persulfate to the lithium salt solution is 1:(5-20).
4. The smart composite material diaphragm according to claim 1, characterized in that: The concentration of the lithium salt solution is 1-2 mol / L; The lithium salt solution is obtained by mixing a lithium salt and a solvent; Preferably, the lithium salt is selected from one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonate)imide, lithium tris(trifluoromethylsulfonate)methyl and lithium bis(trifluoromethylsulfonate)borate; Preferably, the solvent is a carbonate compound, and more preferably, the carbonate compound is selected from one or more of propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
5. The method for preparing the smart composite material diaphragm according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: (1) mixing epoxy resin and D-230 curing agent evenly to obtain a first mixed solution, then infiltrating the first mixed solution into a salt template, and then curing, after the curing is completed, removing the salt template and drying to obtain a shape memory polymer foam skeleton; (2) compressing the shape memory polymer foam skeleton to obtain a compressed shape memory polymer foam skeleton; (3) N-isopropyl acrylamide, acrylamide, N,N'-methylenebisacrylamide, and ammonium persulfate are dispersed in a lithium salt solution to obtain a second mixed solution, and then a compressed shape memory polymer foam skeleton is immersed in the second mixed solution and tetramethylethylenediamine is added to react to obtain an intelligent composite material diaphragm.
6. The preparation method according to claim 5, characterized in that: The curing is firstly curing at 70-90° C. for 1-3 hours, and then curing at 120-140° C. for 1-3 hours.
7. The preparation method according to claim 5, characterized in that: The reaction time is 5 to 10 minutes.
8. The preparation method according to claim 5, characterized in that: The response temperature of the shape memory polymer foam skeleton is 100-150° C.; and / or The response temperature of the gel electrolyte filled in the shape memory polymer foam skeleton is 40-58°C.
9. The preparation method according to claim 5, characterized in that: The intelligent composite material diaphragm has an intelligent autonomous power regulation function and an over-temperature protection function.
10. Use of the smart composite material separator according to any one of claims 1 to 4 or the smart composite material separator prepared by the preparation method according to any one of claims 5 to 9 in a lithium ion battery.
Citation Information
Patent Citations
Gel electrolyte, preparation method thereof, supercapacitor and application thereof
CN110931273A
Polyurethane-based shape memory polymer, polymer electrolyte and preparation
CN113321774A
Preparation method and application of composite material with shape memory characteristic and conductivity capable of being regulated and controlled in multi-stage mode
CN114999702A
Preparation method of gel electrolyte applied to secondary sodium ion battery
CN115775917A
4D printed intelligent variable-structure solid-state lithium ion battery as well as preparation method and application thereof
CN118676421A
Cited By
Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device
CN122051403A